EFFECT OF LIGHT QUALITIES AND STORAGE PERIODS ON THE GERMINATION OF PENNISETUM POLYSTACHION SEEDS*) - S TJITROSEMITO (BIOTROPIA, 1992)
Seeds  of  the  yellowish  inflorescence  strain  of  Pennisetum polystachion,  collected  from  the  field  in Indonesia, were kept  in the dark  for 30 days,  then germinated  in 12-h  light and 24-h  light under various  light qualities, namely, white, black, blue, red and far-red. There was no effect of photo-period to seed germination. Percent of seed germination under white, red, far-red, blue and dark were 49, 43, 22, 11 and 2%, respectively. White and red light did not cause any difference to seed germination. Seeds kept in 12-h light alternating with 12-h dark and 24-h dark for 15 and 30 days were tested for germination. Results  showed  that  light  condition during  seed  storage did not  effect  seed germination.  Long storage period resulted in more seed germination. During seed germination test, effect of light played a great role on increasing seed germination.